Typhlomyrmex meire, a remarkable new species endemic to Southern Bahia, Brazil (Formicidae: Ectatomminae) - Lacau, Sebastien; Villemant, Claire; Delabie, Jacques H.c. (Zootaxa, 2004)
The worker, queen and male of the ant Typhlomyrmex meire Lacau, Villemant & Delabie new spe- cies (Ectatomminae: Typhlomyrmecini) are described from the Brazilian Atlantic rainforest. This endemic species from southern Bahia is easily distinguished from all other members of the genus by the peculiar morphology of mandibles and the reduction of the antennal segments observed in both sexes. We provide a partial redefinition of the genus diagnosis taking into account the antennal structure of the new species. A new identification key for workers is provided.